National rhetorics in the Syrian immigration crisis : victims, frauds, and floods - Tilli, Jouni, 1979-; Rountree, Clarke, 1958- (Rhetoric and public affairs series., 2019)
"The Syrian refugee crisis seriously challenged countries in the Middle East, Europe, the United States, and elsewhere in the world. It provoked reactions from humanitarian generosity to anti-immigrant warnings of the destruction of the West. It contributed to the United Kingdom's "Brexit" from the European Union and the election of Donald Trump as president of the United States. This book is a unique study of rhetorical responses to the crisis through a comparative approach that analyzes the discourses of leading political figures in ten countries, including gateway, destination, and tertiary countries for immigration, such as Turkey, several European countries, and the United States. These national discourses constructed the crisis and its refugees so as to welcome or shun them, in turn shaping the character and identity of the receiving countries, for both domestic and international audiences, as more or less humanitarian, nationalist, Muslim-friendly, Christian, and so forth."--